Bioactive molecule-loaded drug delivery systems to optimize bone tissue repair - Oshiro, João Augusto [UNESP]; Sato, Mariana Rillo [UNESP]; Scardueli, Cassio Rocha [UNESP]; de Oliveira, Guilherme José Pimentel Lopes [UNESP]; Abuçafy, Marina Paiva [UNESP]; Chorilli, Marlus [UNESP] (Bentham Science Publishers, 2017)
Bioactive molecules such as peptides and proteins can optimize the repair of bone tissue; however, the results are often unpredictable when administered alone, owing to their short biological half-life and instability. Thus, the development of bioactive molecule-loaded drug delivery systems (DDS) to repair bone tissue has been the subject of intense research. DDS can optimize the repair of bone tissue owing to their physicochemical properties, which improve cellular interactions and enable the incorporation and prolonged release of bioactive molecules. These characteristics are fundamental to favor bone tissue homeostasis, since the biological activity of these factors depends on how accessible they are to the cell. Considering the importance of these DDS, this review aims to present relevant information on DDS when loaded with osteogenic growth peptide and bone morphogenetic protein. These are bioactive molecules that are capable of modulating the differentiation and proliferation of mesenchymal cells in bone tissue cells. Moreover, we will present different approaches using these peptide and protein-loaded DDS, such as synthetic membranes and scaffolds for bone regeneration, synthetic grafts, bone cements, liposomes, and micelles, which aim at improving the therapeutic effectiveness, and we will compare their advantages with commercial systems.
Keywords: Bioactive molecules; Bone morphogenetic protein; Drug delivery systems; Osteogenic growth peptide; Tissue repair